Using of Optimization Models in Financial Decision Support Systems - Kozlov, V. V.; Tomashevska, T. V.; Kuznetsov, N. I. (Statistics of Ukraine, 2020)
The article discusses the use of optimization models in financial decision support systems (DSS). The architecture of the DSS is considered. It is determined by the nature of the interaction of its main components: the user interface, database and data warehouse, documents and rules, models and analytical tools, communications infrastructure and networks, as well as elements of these parts. The architecture of the DSS for solving problems of financial management is determined by the nature of interaction of its main components. Conceptual and functional models are presented. The functional model of the DSS reflects the structure of control actions on decision-makers, persons involved in the implementation of corrective actions necessary for effective financial performance. According to the functional model, a block diagram of the DSS is proposed. The block diagram of decision support consists of three main subsystems and provides modular-block construction. The proposed system is characterized by an open architecture and can be easily modified for functional expansion or for connecting and using external databases. The DSS should provide a common operating environment for modeling objects in a dynamically changing economic situation. The operating environment contains basic calculation algorithms, and allows the user to create own algorithms for calculating cash flows and used indicators. Thus, the key element of the integrated decision support system for managing the financial condition of the enterprise is the models laid down in the basis of the system. The architecture of the DSS based on algorithms is considered. A DSS of this type contains a set of algorithms for solving a selected class of problems. Of the factors that influence the choice of a specific architecture of the DSS in financial management, we can highlight (i) the need for further development of the system, (ii) its adaptation, and (iii) the application of the evolutionary approach to the development of the DSS. The components of the system are: data input component, resource allocation component, strategy selection component, output component. The resource allocation component contains the following sub-components: determination of dependence coefficients, solution of optimization problem, solution of equation. The strategy selection component includes the sub-components for calculating the values of integral design characteristics, for calculating the values of groups of design characteristics, and for the pairwise comparison of strategies. The information model of the component “The distribution of financial resources of the enterprise” is presented. The DSS performs data processing and checks for critical decision characteristics. The formalized structure of the algorithm for using the proposed models of distribution of financial resources, types of model integration are considered.